FarmBeats: Improving Farm Productivity Using Data-Driven Agriculture - Kapetanovic, Zerina; Chandra, Ranveer; Chakraborty, Tusher; Nelson, Andrew (SIAM News, 2019)
FarmBeats is an end-to-end AI and IoT system for agriculture that helps address these challenges and enable precision agriculture techniques. In particular, FarmBeats gathers data from sensors, cameras, and drones, to produce actionable insights for farmers. Moreover, it can extend Internet coverage to the farm and is resilient towards weather related outages or power variability. Thus far the FarmBeats system has been deployed worldwide, including locations in the United States, India, Africa, and China to name a few. FarmBeats is being used for a variety of agriculture applications such as storage monitoring, generating precision sensor maps of crop fields, animal monitoring, and much more. To get a better understanding of what all FarmBeats encompasses we explain the main components of the system and provide a case study of a FarmBeats deployment on Nelson farm in Spokane, WA.
https://sinews.siam.org/Details-Page/farmbeats-improving-farm-productivity-using-data-driven-agriculture